2020
DOI: 10.7554/elife.60513
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the Ca2+-dependent gating of the human mitochondrial calcium uniporter

Abstract: Mitochondrial Ca2+ uptake is mediated by an inner mitochondrial membrane protein called the mitochondrial calcium uniporter. In humans, the uniporter functions as a holocomplex consisting of MCU, EMRE, MICU1 and MICU2, among which MCU and EMRE form a subcomplex and function as the conductive channel while MICU1 and MICU2 are EF-hand proteins that regulate the channel activity in a Ca2+ dependent manner. Here we present the EM structures of the human mitochondrial calcium uniporter holocomplex (uniplex) in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 52 publications
1
63
0
Order By: Relevance
“…Similar to the C-helix of MICU1, the rigid helix of MICU2 plays a vital role in maintaining the normal threshold under resting conditions (Kamer et al, 2019). To date, a backto-back configuration has been observed in the tetrameric MICU1-MICU2 complex and is the most likely preferred configuration (as further elaborated in the following) (Fan et al, 2020;Wang et al, 2020c;Zhuo et al, 2020). However, the possibility of the other packing configuration cannot be excluded.…”
Section: Structures Of Micusmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar to the C-helix of MICU1, the rigid helix of MICU2 plays a vital role in maintaining the normal threshold under resting conditions (Kamer et al, 2019). To date, a backto-back configuration has been observed in the tetrameric MICU1-MICU2 complex and is the most likely preferred configuration (as further elaborated in the following) (Fan et al, 2020;Wang et al, 2020c;Zhuo et al, 2020). However, the possibility of the other packing configuration cannot be excluded.…”
Section: Structures Of Micusmentioning
confidence: 96%
“…However, extensive subsequent experimental evidence demonstrated that MICU1 and MICU2 could form a stable heterodimer in the absence of disulfide in vitro (Kamer et al, 2017;Li et al, 2016;Wu et al, 2019). Recently, MICU1-MICU2 heterodimer structures were solved by X-ray crystallography, revealing a face-to-face antiparallel assembly (Park et al, 2020;Wu et al, 2020 (Fan et al, 2020;Wang et al, 2020bWang et al, , 2020c. The superimposed structures of Ca 2+ -free and Ca 2+ -bound MICU1-MICU2 heterodimers demonstrate that Ca 2+ -bound structures are more compact than the apo form (Figure 2G).…”
Section: Structures Of the Micu1-micu2 Heterodimermentioning
confidence: 99%
“…The outer mitochondrial membrane shows high permeability to calcium, so that cytosol and intermembrane space calcium concentrations are virtually equal. Calcium enters the matrix via the mitochondrial calcium uniporter (MCU) [ 26 , 27 ] complex on the inner mitochondrial membrane, which shows adaptive response patterns to low-versus-high calcium concentrations [ 28 ]; during diastole, the MCU does not import calcium due to low cytosol concentrations and subsequent blockage by MCU regulatory proteins. Instead, during systole, rising calcium concentrations trigger a conformational change of said proteins, and calcium import is allowed.…”
Section: Mitochondrial Structure and Function In The Normal Heartmentioning
confidence: 99%
“…The acidic residues present in this stretch (in particular E257, D261, E264) are critical for the Ca 2+ transport since, if substituted with uncharged residues, MCU mutants failed to rescue the mitochondrial Ca 2+ uptake in MCU-silenced cells [ 41 , 42 ]. However, the definitive description of MCU 3D structure had to wait till the very last years, when cryo-EM and X-ray diffraction analyses finally allowed the resolution of full-length MCU structure [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. These studies coherently confirmed that purified MCU from different sources (fungi and metazoan) arranges in a tetramer, confuting previous assumptions on a putative pentameric MCU architecture [ 52 ].…”
Section: Discovery and Characterization Of The Mcu Complex Componentsmentioning
confidence: 99%
“…Indeed, MEMMS appears as a 480 kDa integral unit where EMRE coordinates the matrix gate of the MCU channel and MICU proteins interact with the C -terminus of EMRE in the IMS thus enhancing Ca 2+ influx through the MCU pore in high [Ca 2+ ] conditions [ 54 ] ( Figure 3 ). Finally, the distinct Ca 2+ -dependent assembly conformations of the beetle and human MCU holocomplexes with human MICUs have also been detailed [ 46 , 47 ]. In the presence of Ca 2+ , the multiprotein complex shows a two-fold symmetry and consists of two V-shaped MCU-EMRE tetrameric subcomplexes and two MICU1-MICU2 heterodimers that bridge the tops of the subcomplexes ( Figure 1 ).…”
Section: Discovery and Characterization Of The Mcu Complex Componentsmentioning
confidence: 99%